2020
DOI: 10.9734/ajrcs/2020/v5i230091
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Methods: Application in Field Crops and Future Perspectives

Abstract: To reach in good plant stand, the life cycle of plants is faced with different critical stages such as uneven seed germination, poor and early seedling growth which ultimately results in low crop yield. It is well known that seed priming enhances germination, reduces seedling emergence time, and improves yield and yield contributing characters of plants. Seed priming is a physiological technique of seed hydration and drying to improve the metabolic process prior to germination to fasten the germination, seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…In this era, different pretreatment application techniques are widely being used on the emergence and establishment of seedlings. Seed priming is one of the most widely used techniques that promote seed germination, enhance morphological parameters, and improve plant growth and development under non-stress as well as in stress conditions (Muhei, 2018;Rhaman et al, 2020Rhaman et al, , 2021a. Therefore, the present study was conducted on the evaluation of the effects of seed priming and exogenous application SA on the okra plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this era, different pretreatment application techniques are widely being used on the emergence and establishment of seedlings. Seed priming is one of the most widely used techniques that promote seed germination, enhance morphological parameters, and improve plant growth and development under non-stress as well as in stress conditions (Muhei, 2018;Rhaman et al, 2020Rhaman et al, , 2021a. Therefore, the present study was conducted on the evaluation of the effects of seed priming and exogenous application SA on the okra plant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have been reported that seed priming is a promising technique that enhances seed germination and fastens plant growth under normal and as well as in stress conditions by regulating different physiological processes (Muhei, 2018;Hasanuzzaman & Fotopoulos 2019;Rhaman et al, 2020). Similarly, many reports showed that supplementation of SA enhances the growth and yield of many plant species by regulating photosynthetic attributes (Tahjib-Ul-Arif et al, 2018;Gul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different physiological and non-physiological techniques are available for enhancing seed germination as well as alleviating abiotic stresses. Seed priming is a low-cost and effective physiological and biochemical process that stimulates seed germination, enhances morphological parameters, and improves plant growth and development under abiotic stress [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming with hormone solutions is referred to as hormonal priming, and hormonal seed priming plays an important role in seed metabolism [ 9 ]. Currently, hormonal seed priming is a commonly used technique to improve seed germination, seedling growth, and crop yield in adverse conditions [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor soil and high soil temperature will be posed within the alarming climate change in future and seed quality will be a need to be influenced by seed priming (Sivasubramaniam et al, 2011). Hydro priming relies on only soaking of seeds in pure water followed by re-drying to original moisture content prior to sowing making it a low cost and environmentally friendly technique (Rhaman et al, 2020). Uncontrolled water uptake by the seeds during hydro priming is the main limiting factor of hydro priming which results unequal degree of hydration leading to asynchronous metabolic activation within the seeds (Mc Donald, 2000).…”
Section: Future Prospects and Limitationsmentioning
confidence: 99%